Mcdonaldisasi Sebagai Praktik Komunikasi Global (Studi Pola Konsumsi Generasi Z Di Tangerang Selatan) - Fatimatuzahrotul Aini; Annisa Eka Mardiyah (AN-NASHIHA Journal of Broadcasting and Islamic Communication Studies, 2026)
The development of globalization and digital communication technology has transformed patterns of consumption in society, particularly among Generation Z, who live within an instant, fast-paced culture. This phenomenon reflects George Ritzer's concept of McDonaldization, the rationalization of modern life through the principles of efficiency, calculability, predictability, and control. This research is grounded in the aim of understanding McDonaldization not merely as an economic phenomenon, but also as a form of global cultural communication that shapes the social identity of Indonesia's younger generation, focusing on South Tangerang as an urban city with high global cultural penetration. The research objectives include identifying forms of McDonaldization activity within Generation Z's consumption patterns, analyzing the role of social media in reinforcing the spread of global values, and understanding the social and cultural factors driving young people's adoption of consumptive lifestyles. A qualitative descriptive approach was employed through in-depth interviews, participatory observation, and documentation studies, involving 43 Generation Z informants and two supporting informants from communication practitioners and franchise business operators, selected purposively. Data were analyzed using the Miles and Huberman interactive model. This research is expected to produce a conceptual model of global cultural communication based on consumption practices, along with recommendations for consumption literacy among young people amid Indonesia's increasingly digitalized urban society.